The Safe and Nurturing Living Environment for Urban Children - Mariatul Liza Meor Gheda; Habizah Sheikh Ilmi (2019)
As an inheritor of the nation’s future, children should be given the assurance to live and grow in the best possible environment. It is our dream that they would become a persevering, progressive and as well as a well-behaved generation both physically and mentally. In order to achieve that, it is important for the children to be provided with a safe and secure environment to grow up. The research objective is to identify the characteristics of safe and nurturing environment for urban children. The data were collected through focus group interviews with children age 10 and 11 in a research participatory workshop in Sekolah Kebangsaan Seksyen 7, Shah Alam. There were 28 students involved in the workshop. The results indicated the two significant characteristics that promote a safe and nurturing environment for children to roam freely are positive parents and community support. (Abstract by authors)